ChemInform Abstract: First Metal‐ and Base‐Free Selective Oxidative Coupling of Thiols in Neat Ionic Liquids: NMR Probed "Ambiphilic" Character of Neutral [hmim]Br Towards Atom‐Efficient Synthesis of Disulfides. Issue 10 (7th March 2013) - Kumar, Rajesh; Sharma, Nandini; Sharma, Upendra K.; Shard, Amit; Sinha, Arun K.
Abstract The reaction can be applied to aromatic, heteroaromatic and aliphatic mercaptans.